2022
DOI: 10.1371/journal.pone.0270485
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection among vaccinated and unvaccinated: Does it make any difference?

Abstract: Objective There is a probability that vaccination may lead to reduction in the severity and complications associated with COVID-19 infection among hospitalized patients. This study aimed to determine the characteristics, clinical profiles, and outcomes of COVID-19 infection in vaccinated and non-vaccinated patients. Design and data sources This prospective observational cohort study was conducted at the Aga Khan University Hospital (AKUH) and recruited COVID-19 patients admitted between June 1st and Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
2
10
2
Order By: Relevance
“…The results of the current study showed that the level of troponin significantly elevated in the sera of individuals who take the Sinopharm vaccine, Previous studies did not refer to a study of the effect of the Sinopharm vaccine on the level of troponin, but (Zibaeenezhad et al, 2022) indicated an increase in the level of troponin after the first dose of this vaccine for a study of the type of case report. The increase in LDH activity in the present study may be a marker for myocarditis, agreeing with the finding of (Fatima et al, 2022) who indicated that the enzyme activity increased in vaccine recipients, whether it was Pfizer, Sinopharm, Moderna, or others, as well as among people infected with the COVID-19 virus compared to healthy people. While the level of D-dimer didn't show any significant difference after receiving the Sinopharm vaccine.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the current study showed that the level of troponin significantly elevated in the sera of individuals who take the Sinopharm vaccine, Previous studies did not refer to a study of the effect of the Sinopharm vaccine on the level of troponin, but (Zibaeenezhad et al, 2022) indicated an increase in the level of troponin after the first dose of this vaccine for a study of the type of case report. The increase in LDH activity in the present study may be a marker for myocarditis, agreeing with the finding of (Fatima et al, 2022) who indicated that the enzyme activity increased in vaccine recipients, whether it was Pfizer, Sinopharm, Moderna, or others, as well as among people infected with the COVID-19 virus compared to healthy people. While the level of D-dimer didn't show any significant difference after receiving the Sinopharm vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…While the level of ferritin didn't show any significant difference after receiving the Sinopharm vaccine. The elevated level of MDA with reducing in the level of antioxidants represent in GSH in the present study indicates that vaccinations under oxidative stress, in which the antioxidants in the cells such as glutathione improve the immune system and prevent the oxidative processes in the body by removing the toxic materials in the cells such as free radicals or peroxides (Fatima et al, 2022), While the level of peroxy nitrate didn't show any significant difference after receiving the Sinopharm vaccine.…”
Section: Discussionmentioning
confidence: 45%
“…The results of the current study showed that the level of troponin was not affected by the Pfizer vaccine, this result was in disagreement with the finding of (Acharya et al, 2021) which indicates that the level of troponin significantly elevated among Pfizer vaccinators, and they interpreted this increase to the inflammatory and immune response to mRNA vaccine which may be cause myocarditis as one of the conformed side effects of Pfizer vaccine (Marshall et al, 2021;Aye et al, 2021). The increase in LDH activity in the present study may be a marker for myocarditis, and this result agreed with the finding of (Fatima et al, 2022) who indicated that the activity of LDH significantly elevated in sera of individuals who take Pfizer vaccinators. In addition, (Smadja et al, 2021) showed that the level of d-dimer was significantly elevated in the plasma of people who received doses of the Pfizer vaccine, these results agree with the finding of the current study, and this finding indicates that elevated level of D-dimer represents one of the side effects of Pfizer vaccine which activate the coagulation pathways.…”
Section: Discussioncontrasting
confidence: 68%
“…In addition, it seems that some racial and ethnic groups are more prone to comorbidities that predispose them to poorer COVID-19 results, as well as certain unique genetic characteristics that relate the severity of infection with the demographic profile of those groups. Similarly, it is expected that Roma patients are less likely to be vaccinated against COVID-19; therefore, they might have a more severe response to the viral infection [ 24 , 25 , 26 ]. To the best of our knowledge, however, there is a paucity of data about the dynamics of SARS-CoV-2 viral manifestations in the Roma population.…”
Section: Introductionmentioning
confidence: 99%